Development of Interactive Media Based on Augmented Reality for Early Childhood Learning Around the Home - Novaliendry, Dony; Septiawan Saltriadi, Kristiyo; Mahyuddin, Nenny; Sriwahyuni, Titi; Ardi, Noper (International Journal of Interactive Mobile Technologies (iJIM), 2022)
In this age of digitization, it is essential to develop interactive media that may serve as a vehicle for learning while also engaging children. Thus, learning media that includes both real and digital media can be made more exciting and less tedious by making it more fun while still valuing traditional and interactive learning utilizing technology, which is why this is important. This project aims to generate media solutions that early childhood educators and kindergarten teachers can use to assist them in learning and teaching. The media that was created includes Android apps that use Augmented Reality. (AR), technology to make the experience more fun for kids and book media based on the kindergarten curriculum. Subsequently, parents and caregivers can use this media to teach their children about the living room, toilet, and other places based on the images that have been shown. When an Android app scans this picture, it will illustrate animated 3D objects through Augmented Reality. Notwithstanding, the Android app has a free picture coloring option. Equally, it must be supervised by parents or teachers, a practice known as digital parenting. The development and verification results confirm that this medium is suitable for implementation and use in schools and kindergartens.